2021
DOI: 10.3390/ijerph19010396
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Maternal Health Improvement Project in the Louga Region of Senegal

Abstract: Maternal mortality remains a major global health challenge in sub-Saharan Africa. Senegal is one of the countries in the region that lagged behind in reaching the Millennium Development Goal 5, the deadline of which passed in 2015. The objective of this study was to assess the effects of information, education, and communication (IEC) activities conducted in Louga, Senegal. Community groups and facilitators conducted IEC campaigns, home visits, and various awareness-raising activities. This study used secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Specifically, women were motivated to engage in the implementation of interventions, which was ultimately said to strengthen their confidence and decision-making capacity for their health [ 47 ]. Furthermore, a study conducted in Senegal demonstrated significant improvement in women's empowerment as they joined community decision-making groups, easing their decision-making about their healthcare and use of contraception [ 48 ]. Members of WGs in Bangladesh are also reported to have gained more knowledge of ANC issues and new skills in managing their savings [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, women were motivated to engage in the implementation of interventions, which was ultimately said to strengthen their confidence and decision-making capacity for their health [ 47 ]. Furthermore, a study conducted in Senegal demonstrated significant improvement in women's empowerment as they joined community decision-making groups, easing their decision-making about their healthcare and use of contraception [ 48 ]. Members of WGs in Bangladesh are also reported to have gained more knowledge of ANC issues and new skills in managing their savings [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Ethiopia identified relationships between home deliveries and maternal mortality whereas, most women who deliver at home are more likely dying of complications five timely compared to those who took birth in health facilities [6,14,15]. It was also found that, 6% of maternal death in India were those delivered from home [14,16]. This is because home do not provide conducive environment for childbirth services due to lack of skilled personnel, hygiene and no equipment to support delivery procedures or delivery complications.…”
Section: Home Deliverymentioning
confidence: 99%
“…Through the adoption of the SDGs, Senegal government has committed to achieving the SDG5 goal which set 170 maternal deaths per 100,000 live births as its target. To achieve the SDGs and in line with Senegal's national policy based on the National Health Development Plan (PNDS), the country has made considerable efforts by launching several programs to reduce the burden of maternal, neonatal, and infant mortality 14 . The Government of Senegal has also implemented programs for universal primary education, adult literacy integrated into national development plans, the eradication of illiteracy, and the promotion of local languages to accelerate the promotion of access to basic social services 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the SDGs and in line with Senegal's national policy based on the National Health Development Plan (PNDS), the country has made considerable efforts by launching several programs to reduce the burden of maternal, neonatal, and infant mortality. 14 The Government of Senegal has also implemented programs for universal primary education, adult literacy integrated into national development plans, the eradication of illiteracy, and the promotion of local languages to accelerate the promotion of access to basic social services. 15,16 Thus, adult literacy rate rose from 39.3% in 2002 to 51.9% in 2017, more important for men than women.…”
Section: Introductionmentioning
confidence: 99%